(untitled) (CAHIERS MAGELLANES-NS, 2024)
Marine algae are an important source of bioactive metabolites in drug development and nutraceuticals. Due to changes in lifestyle brought on by increasing urbanization, diabetes mellitus, a metabolic illness, is currently the third largest cause of mortality globally. Seeking an efficient natural-based antidiabetic medication is crucial to battling diabetes and associated consequences because the existing antidiabetic medicines have unfavorable side effects. Brown algae are among the marine seaweeds that have a large number of naturally occurring bioactive chemicals that may be used as active ingredients in pharmaceuticals and nutraceuticals. Brown algae-derived polyphenols also have the potential to lessen the problems associated with diabetes. The antidiabetic activity will be investigated using the alpha-amylase enzyme inhibition test. The antioxidant properties were determined by total antioxidant assays, Hydrogen peroxide assay and DPPH scavenging. Hence, the present study focuses on the antidiabetic and antioxidant activity of secondary bioactive compounds present in marine brown algae.